DMF Index among Amelogenesis Imperfecta Patients: Systematic Review of the Literature - Farah Kallel; Amel Labidi; Sana Bekri; Sinda Ammar; Sonia Ghoul; Lamia Mansour (International Journal of Dentistry)
Objectives. The aim of this study was to explore the literature in order to assess systematically the association between amelogenesis imperfecta (AI) and caries development and to evaluate the DMF index among AI patients. Basic Research Design. PubMed was used to explore the database Medline. The key words used were “Amelogenesis Imperfecta” [Mesh], “Dental Caries” [Mesh], “Tooth Loss” [Mesh], “DMF Index” [Mesh], and “Dental Restoration, Permanent” [Mesh]. Moreover, an ad hoc search was performed in order to make the study as exhaustive as possible. Results. Fifty-five articles were retained. The total number of patients gathered was 499. A percentage of 68.8% of the articles dealt with cases with a relatively low dental caries process, 20.8% dealt with cases in which the dental caries process was relatively moderate, and 10.4% dealt with cases in which the dental caries process was severe. Teeth extraction due to dental caries was mentioned in 10 articles. Eleven articles, concerning 53 patients, mentioned dental fillings. Four patients did not have dental filling due to dental caries. DMF index was very low in 2 articles and low-to-high in 3 articles. Conclusion. Low dental caries susceptibility with AI patients was noticed in this study. A possible factor could be the lack of proximal contacts and elimination of fissures through enamel loss. The lack of dental caries susceptibility was also explained by the microbacterial specificity of hypoplastic AI patients. Moreover, it was also noted that the prevalence of dental caries among AI patients depends on sociodemographic change.